An evaluation of the available methods of selecting a contractor, in order to satisfy the client's objectives, with a view to offering a systematic approach to which method should be adopted - Stevenson, Colin (Department of Construction Economics and Management, 2018)
Although the client's objectives of balancing cost, time and performance have not changed, the complexity of the design and construction of modern buildings today requires a thorough understanding of the factors affecting these objectives if they are to be accomplished. This study therefore begins by analysing the client's objectives to establish the factors affecting each objective and to determine the inter-relationship and possible conflict between these factors. The principal types of contracts and methods of selecting a contractor are then identified. The methods of selecting a contractor are then evaluated according to these factors and their effects on the client's objectives are established. This evaluation is then used as the basis for recommending a procedure to choose which method should be used to select a contractor, in order to accomplish the client's objectives, under differing circumstances.